The Effect of Health Banks on Share Returns in Banking Companies Listed on the IDX for the 2019 Period With Political Events (Indonesia Presidential Elections) as Dummy Variables - Roby Hadimurzani; Ardi Paminto; Irwansyah Irwansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The capital market as an economic instrument is inseparable from environmental influences, both the economic environment and the non-economic environment. Political events are one of the non-economic risks that can influence investors' decisions to invest in the capital market. The purpose of this study is to determine the effect of political events in Indonesia in 2019 on stock returns during the Campaign Period & Presidential and Vice Presidential Elections along with the election of members of the DPR, DPD, Provincial DPRD, and Regency / City DPRD until their inauguration period on listed banking company stocks. On the Indonesia Stock Exchange. With the research title "The effect of bank health on stock returns in banking companies listed on the IDX for the 2019 period with political events (Indonesian Presidential Election) as a dummy variable. This research shows that the presidential election events in 2019 have no significant effect on the stock returns of banking companies that book IV. The results show that of the six (6) variables only two (2) have a significant positive effect, namely the ROA and CAR variables, the authors conclude that companies with capital capitalization above IDR 30 Trillion (Book IV) are not easily shaken or relatively stable. What investors are often familiar with is the Blue Chip stock, which has implications for stock returns to investors.